COST MANAGEMENT: THE USE OF FIRE FOR PASTURE RENEWAL IN ALTO MINHO - Rodrigues, Paulo; Barreiro, Paulo (Floresta, 2023)
Portugal has been the target of large fires in recent years. There is no exception for the Alto Minho region, which year after year is ravaged by fire. This territory is characterized by the misfortune of occupying a prominent place in number of occurrences and burned area. Nevertheless, it brings together some peculiarities, which make it a unique territory. It is in relation to fire and one of its particularities that this study focuses: the fires for renovation of pastures in Alto Minho. Annually this cause of fire is around 10% of the total number of occurrences, but it may be responsible for more than 50% of the burnt area. Quantifying the cost of fighting these fires could be an initial way to alert and try to reverse a process with hundreds of years whose results are increasingly catastrophic. The values found in this investigation are high in relation to the reference value, so a change to the procedure as a whole is urgent, as a solution within the territory itself.